2018
DOI: 10.1007/s11250-018-1751-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine viral diarrhea virus in dairy cattle herds in eastern China

Abstract: Bovine viral diarrhea virus (BVDV) is a worldwide spreading pestivirus affecting cattle and other ruminants; however, there have been few reports on epidemiologic investigation of BVDV in eastern China. In this study, bulk tank milk from 36 herds of dairy cattle in eastern China was submitted to serological investigations, 77.8% of herds was BVDV antibody positive. Individual animal status in two herds was further investigated collecting blood samples, the positive ratio was 49.74% and 24.64%, and the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 44 publications
0
17
0
8
Order By: Relevance
“…In China, BVDV-1a and -1c have been commonly detected in different regions of China. Recently, BVDV-1c (7/9) and BVDV-1a (1/9) strains were detected from 36 herds of dairy cattle in 5 provinces in eastern China [ 29 ]. A recent analysis of 119 BVDV sequences obtained from 92 dairy farms showed that subgenotypes of BVDV-1a ( n = 37, 31.09%), BVDV-1c ( n = 34, 28.57%) and BVDV-1 m ( n = 25, 21.01%) were predominant in 19 provinces of China in 2017 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, BVDV-1a and -1c have been commonly detected in different regions of China. Recently, BVDV-1c (7/9) and BVDV-1a (1/9) strains were detected from 36 herds of dairy cattle in 5 provinces in eastern China [ 29 ]. A recent analysis of 119 BVDV sequences obtained from 92 dairy farms showed that subgenotypes of BVDV-1a ( n = 37, 31.09%), BVDV-1c ( n = 34, 28.57%) and BVDV-1 m ( n = 25, 21.01%) were predominant in 19 provinces of China in 2017 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…BVDV is one of the most important viruses affecting bovine species throughout the world (1)(2)(3)(4). It is a complex cocktail of two strains of the virus inducing various clinical syndromes of the affected animals (5).…”
Section: Introductionmentioning
confidence: 99%
“…Pestivirus A (BVDV-1), Pestivirus B (BVDV-2), and Pestivirus H (HoBi-like Pestivirus) are the major pestiviruses infecting bovine species (ICTV 2019). Furthermore, there are at least 23 subgenotypes of BVDV-1 (1a-1w) and four subgenotypes of BVDV-2 (2a-2d) (Deng et al 2020, Hou et al 2019. BVDV can exist in two different biotypes based on its effects on infected cell cultures: cytopathic (cp) and non-cytopathic (ncp) (Baker 1995).…”
Section: Introductionmentioning
confidence: 99%